GAMBARAN AKTIVITAS FISIK PADA PEMAIN MOBILE LEGEND DI TIM E-SPORT UPN VETERAN JAKARTA - Sheila Rindu Prameswari, (2022)
Developments in the digital era have brought changes in all aspects, including sports, which have grown rapidly to give birth to e-sports. Currently, the most popular e-sport game is mobile legend, legend mobile game players do not look at the age ranging from children to adults. Characteristics of mobile legend e-sport players are less concerned with the surrounding environment, lazy, do not regularly do sports and prefer to stay long in a sitting or lying position so that it affects the level of daily physical activity. The purpose of this study was to examine the description of the physical activity of mobile legend players in the UPN Veteran Jakarta e-sports team. The research was conducted using a quantitative descriptive research method with a Cross-Sectional Study approach. The sample required is as many as 80 samples with the selection of samples using a purpose sampling technique. The parameter used is the International Physical Activity Questionnaire (IPAQ). The results showed that the mobile legend players on the e-sports team on average did physical activity in the light category as many as 40 respondents (50%).